Platelet Shape Changes during Thrombus Formation: Role of Actin-Based Protrusions - Bender, Markus; Palankar, Raghavendra (Hämostaseologie, 2021)
Platelet activation and aggregation are essential to limit blood loss at sites of vascular injury but may also lead to occlusion of diseased vessels. The platelet cytoskeleton is a critical component for proper hemostatic function. Platelets change their shape after activation and their contractile machinery mediates thrombus stabilization and clot retraction. In vitro studies have shown that platelets, which come into contact with proteins such as fibrinogen, spread and first form filopodia and then lamellipodia, the latter being plate-like protrusions with branched actin filaments. However, the role of platelet lamellipodia in hemostasis and thrombus formation has been unclear until recently. This short review will briefly summarize the recent findings on the contribution of the actin cytoskeleton and lamellipodial structures to platelet function.
Keywords: platelet; thrombus; cytoskeleton; lamellipodia; actin